PERLINDUNGAN HUKUM TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA NARKOTIKA (STUDI KASUS DI PENGADILAN NEGERI DENPASAR) - Kartika Setiawan, I Wayan; Mertha, I Ketut; Suardana, I Wayan (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 04, September 2013)
Law protection on the children as performer of narcotic criminal act necessarybecause considers their mental and psychiatric that different with adults. This lawprotections is very important to do in order to protect the child rights to grow, develop,participate optimally in accordance with the dignity of humanity, and get protection toviolence and discrimination. Law protection can be applied through discretion of Polri,public prosecutor and also court decision that by sanction of performer actions ofnarcotic crime the children can recover physically and mentally whithout havingprosecuted criminal sanctions. Thus, all matters relate to the freedom and child humanrights and the various interests of the child prosperity which is the purpose of the cildlaw protection can be met properly.
Keywords: Law Protection, Child, Narcotics Crime Act